Process variables : four common elements of counseling and psychotherapy - Walborn, Frederick S., 1955- (Brooks/Cole, 1996)
This volume introduces theories and research regarding four process variables - therapeutic relationship, client expectations, emotional expression and experiencing, and cognitive insight - and demonstrates the link between research and applied psychology.